Investigation of Strength and Consolidation Behaviour of Peat Treated Using Microbial-Induced Calcite Precipitation (MICP) - Phang, Ignatius Ren Kai (Curtin University, 2021)
The study of Microbial-induced carbonate precipitation (MICP) on organic soil has remained limited. This PhD study intends to fill the knowledge gap by studying MICP of tropical peat. Based on the finding, it was possible (i) to isolate bacteria strains from acidic tropical peat with high urea hydrolysis activities and capable of bio-cementation; (ii) to induce bio-cementation in acidic peat, which leads to strength gain and reduction of permeability; (iii) to improve consolidation behaviour.